Pengaruh Budaya, Etos Kerja dan Kinerja terhadap Hasil Produksi pada PT. Marimas Putra Kencana - Soegihartono, Soegihartono (Jurnal Riset Rumpun Ilmu Ekonomi, 2024)
This study aims to analyze the influence of work culture, work ethic, and employee performance on production results within an organization. Data were collected through a survey of employees and analyzed using linear regression to examine the relationship between independent and dependent variables. The results indicate that employee performance and work ethic have a positive and significant impact on production results, meaning that the better the performance and work ethic of employees, the higher the production output achieved. Conversely, work culture shows a negative effect on production results, suggesting that certain aspects of the existing work culture may need improvement to better support productivity enhancement. The regression model used in this study demonstrates that work culture, work ethic, and employee performance can explain a significant portion of the variation in production results, although other external factors may also contribute. Therefore, organizations need to evaluate their existing work culture and develop strategies to improve work ethic and employee performance. Measures such as training programs, incentive schemes, and improvements in the work environment can help optimize productivity and enhance production outcomes.